Effects of Overt and Covert Motivational Self-talk on Performance and Perceived Exertion Rate of Wrestlers in Progressive Exhaustion Exercise - Mohammad Sadegh Afroozeh; Hasan Mohammadzadeh Jahatloo; Mostafa Edrisi Kolur; Ali Afroozeh (University of Tehran, 2014)
The aim of this study was to examine the effect of overt and covert motivationalself-talk on perceived exertion and performance in a progressive exercise untilexhaustion in wrestlers. The population consisted of wrestlers in Urmia and 15volunteer subjects were selected. This study was performed in three sessions with aone-week interval. The first session was held without self-talk while the second andthird sessions were held covertly and overtly respectively. Bruce aerobic exercisetest was used in this study as well. The time to exhaustion was considered asperformance. Burg scale was used every 3 minutes in order to measure subjects'exhaustion. To analyze the data, ANOVA with repeated measures and TUKEY posthoc test was used. The results showed that only covert self-talk had a significanteffect on subjects' performance (P=0.002). Also, overt motivational self-talk(P=0.001) significantly decreased the subjects' perceived exertion rather thancovert self-talk. There was no significant difference between covert self-talk andwithout self-talk (P=0.121). In conclusion, overt motivational self-talk decreasedthe perceived exertion of the subjects in the progressive exercise until exhaustionwhile covert motivational self-talk improved subjects' endurance.